2016
DOI: 10.1175/mwr-d-16-0063.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Wind Predictions in the Marine Atmospheric Boundary Layer through Parameter Estimation in a Single-Column Model

Abstract: A current barrier to greater deployment of offshore wind turbines is the poor quality of numerical weather prediction model wind and turbulence forecasts over open ocean. The bulk of development for atmospheric boundary layer (ABL) parameterization schemes has focused on land, partly because of a scarcity of observations over ocean. The 100-m FINO1 tower in the North Sea is one of the few sources worldwide of atmospheric profile observations from the sea surface to turbine hub height. These observations are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Although past use of simplified physical models and basic observational technology has allowed for installation of wind power plants and predictions of performance in a variety of terrain types, there are still major gaps in our knowledge about wind flows in complex terrain or under varying atmospheric stability conditions that can change over the course of a day or season (34,36). Moving to offshore wind power introduces additional coupled physics of the meteorological-oceanographic (i.e., the "metocean") environment, where a nontrivial modeling uncertainty remains, especially with breaking or irregular waves, atmospheric stability, and tropical storms (37).…”
Section: First Grand Challenge: Improved Understanding Of Atmosphericmentioning
confidence: 99%
“…Although past use of simplified physical models and basic observational technology has allowed for installation of wind power plants and predictions of performance in a variety of terrain types, there are still major gaps in our knowledge about wind flows in complex terrain or under varying atmospheric stability conditions that can change over the course of a day or season (34,36). Moving to offshore wind power introduces additional coupled physics of the meteorological-oceanographic (i.e., the "metocean") environment, where a nontrivial modeling uncertainty remains, especially with breaking or irregular waves, atmospheric stability, and tropical storms (37).…”
Section: First Grand Challenge: Improved Understanding Of Atmosphericmentioning
confidence: 99%
“…Sensitivity experiments have seldom been conducted to investigate the relationship between the different variables. Sterk et al (2015) and Lee et al (2017) suggested that compared to the atmospheric three-dimensional dynamics in the WRF model, the WRF-SCM provides a platform for more rapid testing and is a more useful tool to evaluate the sensitivities of various parameters and schemes in NWP models without the interference of three-dimensional atmospheric dynamics. So far, WRF-SCM has been used in some sensitivity experiments (e.g., Baas et al, 2010;Sterk et al, 2015;Svensson et al, 2011), but few of these experiments have paid attention to changes in SM and land use.…”
Section: Sensitivity Experiments With a Scmmentioning
confidence: 99%
“…The responsibility of providing the timely information lies with the air quality managers across the United States, who provide this information by analyzing air quality and weather observations along with Numerical Weather Predictions (NWPs) and PM 2.5 guidance from the National Air Quality Forecasting Capability (NAQFC). The NAQFC uses a state‐of‐the‐science chemistry transport model (CTM) called the Community Multiscale Air Quality (CMAQ) model to predict PM 2.5 (Lee et al, ). CMAQ employs advanced numerical procedures and sophisticated algorithms to process emission inventories and parameterizes a variety of atmospheric physical and chemical processes to predict concentrations of air pollutants including PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%